2015
DOI: 10.1111/age.12323
|View full text |Cite
|
Sign up to set email alerts
|

Progressive retinal atrophy in Shetland sheepdog is associated with a mutation in the CNGA1 gene

Abstract: Progressive retinal atrophy (PRA) is the collective name of a class of hereditary retinal dystrophies in the dog and is often described as the equivalent of retinitis pigmentosa in humans. PRA is characterized by visual impairment due to degeneration of the photoreceptors in the retina, usually leading to blindness. PRA has been reported in dogs from more than 100 breeds and can be genetically heterogeneous both between and within breeds. The disease can be subdivided by age at onset and rate of progression. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
(23 reference statements)
0
20
0
Order By: Relevance
“…Although no functional characterization of these mice has been reported, histological analysis revealed some morphological features of RP (e.g., reduced number of photoreceptors, apoptotic death of retinal cells). A naturally occurring Cnga1 mutation has been recently identified in a Shetland sheepdog breed with progressive retinal atrophy [ 54 ]. However, functional characterization of the retinal phenotype is still missing.…”
Section: In Vivo Analysis Of Cng Channel Function: Analysis Of Genmentioning
confidence: 99%
“…Although no functional characterization of these mice has been reported, histological analysis revealed some morphological features of RP (e.g., reduced number of photoreceptors, apoptotic death of retinal cells). A naturally occurring Cnga1 mutation has been recently identified in a Shetland sheepdog breed with progressive retinal atrophy [ 54 ]. However, functional characterization of the retinal phenotype is still missing.…”
Section: In Vivo Analysis Of Cng Channel Function: Analysis Of Genmentioning
confidence: 99%
“…Progressive retinal atrophy (PRA) is a collective term that describes a multitude of inherited retinal degenerations observed in dogs and cats. PRA is often considered to be the canine equivalent of retinitis pigmentosa (RP) which occurs in humans [ 11 ]. Interestingly this group of inherited retinal degenerations is diverse and affect a congregation of genes, they do not follow a single model of inheritance, but have many variations, and the age of onset ranges greatly.…”
Section: Introductionmentioning
confidence: 99%
“…Genome wide association studies in dogs have been highly successful owing to long-range linkage disequilibrium (LD), available SNP genotyping tools and a robust genome assembly [ 17 , 18 ]. There are many examples of successful GWAS in dogs for Mendelian traits [ 17 , 19 , 20 , 21 , 22 , 23 ] as well as for more complex traits [ 24 , 25 , 26 , 27 , 28 ]. In addition, across-breed mapping studies by us and others have successfully identified biologically relevant loci for several traits and related diseases that are fixed within breeds [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%